ANALISIS KANDUNGAN ZAT GIZI NUGGET IKAN KURISI (Nemipterus Nematophorus) SUBTITUSI BUAH LAMUN (Enhalus Acoroides) UNTUK MEMPERBAIKI MASALAH GIZI PADA MASYARAKAT PULAU - Irviani A. Ibrahim; Emmi Bujawati; Mirnawati Mirnawati (Media Gizi Pangan, 2017)
Background: Nugget is a popular food and fancied by community in various age groups, including school-age children and It is one of the most favorite and trendy foods. The raw materials used in nuggets in this study are Kurisi fish (Nemipterus nematophorus) and seagrass (Enhalus acoroides). The study is aimed at determining the nutrient contents (carbohydrate, protein, fat, calcium, Fe, and Phenol) and organoleptic test on kurisi fish nugget (Nemipterus nematophorus) substitute product of seagrass (Enhalus acoroides).Method: The design type of the research is complete randomized design as it is applied to experiments conducted in a homogeneous environment and the research approach used is an experimental approach using true-experimental design. Methods used for the treatment of kurisi fish (Nemipterus nematophorus) and seagrass (Enhalus acoroides) by comparing the experimental group 1:0 (100 gr kurisi fish), 3:1 (75 gr of fish and 25 gr seagrass), 1:1 (50 gr fish and 50 gr seagrass), and 1:3 (25 gr fish and 75 gr seagrass).Result: The results reveal that 4 different concentration treatments are conducted by adding the seagrass (Enhalus acoroides) i.e. 1: 0:1: 1:3: 1 and 1:3 with 3 repetitions. The results of carbohydrate are 32.35%, protein 13.74%, fat 14.04%, calcium 33.03 ug/g, Fe 35.24 ug/g and Phenol 2699.47 ug/g. The most favorable organoleptic test and good quality is 1:0 treatment. Keywords: Nugget, Kurisi Fish (Nemipterus nematophorus), Seagrass (Enhalus acoroides), Nutrition